Peran Guru dalam Mengurangi Rasa Takut Anak Saat Beradaptasi Lingkungan Baru di TK Uswatun Hasanah - Susi Adriyanti; Naufal Muadz Dinata; Fitriyani; Fida Nurmasari Lubis; Rika Widya (Medan Resource Center, 2025)
The adaptation process of early childhood to the school environment is a crucial developmental stage often accompanied by fear and anxiety, particularly during the initial period of school entry. These emotional responses can affect children’s comfort, classroom participation, and social-emotional development. However, previous studies have tended to discuss early childhood adaptation in general terms and have rarely provided contextualized analyses in specific kindergarten settings, including TK Uswatun Hasanah, indicating a gap in localized empirical research. This study aims to describe the forms of fear experienced by young children during the adaptation process and to examine the role of teachers in reducing children’s fear in the new school environment. This research employed a qualitative descriptive design involving five kindergarten teachers as key informants. The study was conducted over three months during the first semester of the academic year. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing, with triangulation to ensure validity. The findings reveal that children’s fear was manifested through crying, reluctance to enter the classroom, limited interaction, and refusal to participate in activities. The study contributes an emotionally based adaptation approach model emphasizing emotional security, teacher-child attachment, and structured play. These findings imply the importance of emotionally responsive teaching strategies to support smoother early childhood school adaptation.